2016
DOI: 10.3389/fpsyg.2016.01624
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Conflicting Age and Wealth Cross-Categorization: The Dominant Role of Categories That Violate Stereotypical Expectations

Abstract: The purpose of the current study was to identify the functional significance of conflicting stereotypes and to identify the dominant category in such conflicts. In the present research we examined the conflicting crossed categories of age and wealth with regard to warmth and competence perceptions. It was found (Pilot Study and Study 1) that the old-rich targets presented a conflicting stereotype group in the perception of warmth, whereas young-poor targets presented a conflicting stereotype group in the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Few studies have compared the weight of categories with social clues and categories with natural clues. One exception is a study by Song & Zuo (2016a) who found that the functional significance of age was greater than wealth when evaluating warmth, while wealth played a more significant role than age when evaluating competence.…”
Section: Comparing the Weight Of Simple Categories With Natural And Smentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies have compared the weight of categories with social clues and categories with natural clues. One exception is a study by Song & Zuo (2016a) who found that the functional significance of age was greater than wealth when evaluating warmth, while wealth played a more significant role than age when evaluating competence.…”
Section: Comparing the Weight Of Simple Categories With Natural And Smentioning
confidence: 99%
“…The perception and evaluation of a target is substantially impacted by their social (occupation and wealth) and cultural identity (Song & Zuo, 2016a). Many previous studies have focused on wealth, with results showing that people, even children, prefer individuals of high socioeconomic status.…”
Section: Comparing the Weight Of Simple Categories With Natural And Smentioning
confidence: 99%
See 3 more Smart Citations